Nitrogen isotope pattern in Mongolian larch stands at the southern Eurasian boreal forest boundary. Issue 6 (2nd November 2018) - Hayashi, Mika; Lopez Caceres, Maximo Larry; Nobori, Yoshihiro; Mijidsuren, Byambasuren; Boy, Jens
ABSTRACT: In the last decades a drastic increase in air temperature but a stable precipitation regime in Mongolia has led to gradual drying conditions. Thus, we evaluated the effect of spatial and climatic characteristics on the soil–plant nitrogen dynamics in three representative larch stands ( Larix sibirica ) with different geographical and climatic conditions using stable nitrogen isotopes. The results showed significant differences in the soil inorganic N content among sites and consequently a different isotopic composition in the plant–soil system. Litter, bark and wood had the lowest δ 15 N values for all sites, slightly higher δ 15 N values for needles, while the highest δ 15 N values were observed for roots and soil. These differences could be the result of the larch stands age themselves, but were in agreement with the spatial and climatic characteristics of the sites. Based on the δ 15 N value a higher reliance on ectomycorrhizal fungi (ECMF) was observed in the warmest and driest site, while lower dependency was shown in the cooler northern site with higher soil inorganic N content. In both sites, the rate of air temperature increase has been similar in the last decades; however, their soil–plant N dynamics showed different characteristics.